The Effectiveness of Physical Fitness Exercise Towards Cognitive Disorders in the Elderly (Department of Physical Education, Sport, Health and Recreation, 2023)
Cognitive disorder in the elderly causes an economic burden on the family and less independence from the elderly. Cognitive decline will be a serious threat to the quality of life of the elderly. The purpose of this study was the effect of physical fitness gymnastics on cognitive impairment in the elderly for gymnastics participants in the Padang Sappa field, Ponrang sub-district. The design of this research is a qualitative descriptive with data collection techniques of unstructured interviews or free interviews where the researcher does not have to use interview guidelines that have been arranged systematically and completely. The approach taken is a phenomenological approach that brings to experience, by exploring and understanding the object of research. Sample selection is based on age 55 and over according to the World Health Organization (WHO). The results of this research show that the elderly who joins the gymnastic are still capable of following, asseting, and remembering the movements from the instructor, and from the interview results show that the elderly still have good responses which show that the cognitive function is still good in doing activities and thinking.